Identification of Bacterial and Viral Codetections With Mycoplasma pneumoniae Using the TaqMan Array Card in Patients Hospitalized With Community-Acquired Pneumonia. (30th March 2016) - Diaz, Maureen H.; Cross, Kristen E.; Benitez, Alvaro J.; Hicks, Lauri A.; Kutty, Preeta; Bramley, Anna M.; Chappell, James D.; Hymas, Weston; Patel, Anami; Qi, Chao; Williams, Derek J.; Arnold, Sandra R.; et al.
Abstract: Mycoplasma pneumoniae was detected in a number of patients with community-acquired pneumonia in a recent prospective study. To assess whether other pathogens were also detected in these patients, TaqMan Array Cards were used to test 216 M pneumoniae -positive respiratory specimens for 25 additional viral and bacterial respiratory pathogens. It is interesting to note that 1 or more codetections, predominantly bacterial, were identified in approximately 60% of specimens, with codetections being more common in children.